Chronic effects of inflammation on tauopathies. Issue 5 (May 2023) - Langworth-Green, Connor; Patel, Saisha; Jaunmuktane, Zane; Jabbari, Edwin; Morris, Huw; Thom, Maria; Lees, Andrew; Hardy, John; Zandi, Michael; Duff, Karen
Summary: Tauopathies are a heterogeneous group of neurodegenerative disorders that are characterised by the aggregation of the microtubule-associated protein tau into filamentous inclusions within neurons and glia. Alzheimer's disease is the most prevalent tauopathy. Despite years of intense research efforts, developing disease-modifying interventions for these disorders has been very challenging. The detrimental role that chronic inflammation plays in the pathogenesis of Alzheimer's disease is increasingly recognised; however, it is largely ascribed to the accumulation of amyloid β, leaving the effect of chronic inflammation on tau pathology and neurofibrillary tangle-related pathways greatly overlooked. Tau pathology can independently arise secondary to a range of triggers that are each associated with inflammatory processes, including infection, repetitive mild traumatic brain injury, seizure activity, and autoimmune disease. A greater understanding of the chronic effects of inflammation on the development and progression of tauopathies could help forge a path for the establishment of effective immunomodulatory disease-modifying interventions for clinical use.